2019
DOI: 10.1096/fj.201901671r
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fusion mediated by fusion promotion and fission inhibition directs adult mouse heart function toward a different direction

Abstract: Mitochondrial fusion and fission are essential for heart function. Abrogating mitochondrial dynamism leads to cardiomyopathy. Excessive mitochondrial fragmentation is involved in most heart diseases, thus enhancing mitochondrial fusion will be a potential therapeutic strategy. To understand the effects of promoting mitochondrial fusion in adult cardiac, we investigated mice hearts, and cultured murine embryonic fibroblasts (MEFs), in which mitofusin 2 (Mfn2) overexpressed or dynamin-related protein 1 (Drp1) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…They found that mitochondria in Mfn-1-deficient hearts were smaller than those in Mfn-2deficient hearts, and the proportion of enlarged mitochondria in Mfn-2-deficient hearts became more tolerant to Ca 2+ -induced mitochondrial permeability transition pore (MPTP) opening (Fang et al, 2007). Our investigations indicated that Mfn2 overexpression could maintain cardiac mitochondrial function by increasing mitochondrial biogenesis from mitochondrial dysfunction-induced cardiotoxicity (Qin et al, 2020). It has been reported that Mfn2 also plays a vital role in Parkin-mediated mitochondrial autophagy, which is essential for mitochondrial quality control and cardioprotection (Gong et al, 2015b;.…”
Section: Cardiac Hypertrophy and Heart Failurementioning
confidence: 62%
See 1 more Smart Citation
“…They found that mitochondria in Mfn-1-deficient hearts were smaller than those in Mfn-2deficient hearts, and the proportion of enlarged mitochondria in Mfn-2-deficient hearts became more tolerant to Ca 2+ -induced mitochondrial permeability transition pore (MPTP) opening (Fang et al, 2007). Our investigations indicated that Mfn2 overexpression could maintain cardiac mitochondrial function by increasing mitochondrial biogenesis from mitochondrial dysfunction-induced cardiotoxicity (Qin et al, 2020). It has been reported that Mfn2 also plays a vital role in Parkin-mediated mitochondrial autophagy, which is essential for mitochondrial quality control and cardioprotection (Gong et al, 2015b;.…”
Section: Cardiac Hypertrophy and Heart Failurementioning
confidence: 62%
“…Drp1 is an essential protein that modulates abnormal mitochondrial fission to generate a healthy and an unhealthy daughter mitochondria; the latter is removed by mitophagy to avoid accumulation of unhealthy mitochondria (Elgass et al, 2013). By combining Drp1 and cardiac myocytetargeted Cre alleles in mice with cardiac Drp1 knockout, it was shown that the inhibition of fission ultimately resulted in a loss of cardiac myocyte mitochondria and lethal dilated cardiomyopathy (Dorn et al, 2015;Qin et al, 2020). In IRI, Drp1 activity is influenced by calcineurin, a heterodimeric protein involved in the transduction of a variety of Ca 2+ -mediated signals (Zou et al, 2001;Cribbs and Strack, 2007).…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Excessive mitochondrial fragmentation is involved in most heart diseases, thus, enhancing mitochondrial fusion will be a potential therapeutic strategy. The latest research found mitochondrial fusion provoked by fusion promotion and fission inhibition direct the different fate of heart, Mfn2 upregulation other than Drp1 downregulation well maintains heart mitochondrial function is a more safe strategy for correcting excessive mitochondrial fragmentation in hearts [31]. Maneechote's team intervened rats with ischemia-reperfusion using mitochondrial fusion promoter M1 (2 mg/kg).…”
Section: Effects Of Mitochondrial Dynamic Imbalance On the Organismmentioning
confidence: 99%
“…Pressure-overload HF murine models have been described to have an mitophagic blockade, which causes damaged mitochondria to accumulate and mitochondrial dysfunction to ensue (Yu et al, 2018). Regarding the different states of the mitochondrial network, fused mitochondria predomination has been described to be beneficial for cardiac function (Wai et al, 2015;Qin et al, 2020), as they are better at ATP synthesis and have lower ROS generation. Following this train of thought, inhibiting fission, promoting fusion, or maintaining an adequate mitophagy profile could potentially protect cardiac electrical signaling and organization.…”
Section: Mitophagy In Cardiac Arrhythmiamentioning
confidence: 99%